Differential editing efficiencies in cereal crops: a comparative analysis of tRNA and ribozyme multiplexed guide delivery - Milner, Matthew J.; Sharma, Manisha; Bates, Ruth E.; Whiting, Michelle; Craze, Melanie S.; Miller, Peter; Brooks, Jack; Kouidri, Allan; Wallington, Emma J. (Frontiers in Plant Science, 2024)
Cereal transformation and gene editing can be a complex and costly undertaking. It is therefore important to validate and understand the performance of the components to achieve high rates of transformation and gene editing. Here, we have made a direct comparison of different CRISPR/Cas9 guide systems to target the genome in three cereal species. We show that the guide sequences driven by the same pol II promoter in rice, wheat and barley show large differences in editing efficiency. The differences seen were based on the way the guides were presented and factors outside of the guide sequence itself. While both the tRNA system and ribozyme system performed well in rice, their effectiveness varied in wheat and barley. Specifically, the tRNA system outperformed the ribozyme system, achieving higher rates of editing in stable transformed plants. Overall, high levels of editing are observed in all three species when strong expression of the SpCas9 is coupled with the CmYLCV promoter to drive a tRNA array of guide RNAs. Stable inheritance is also achievable in all three species when plants are sampled shortly after the tissue culture concludes. Overall, inheritance rates were above 85% in all three species, particularly when mutations are detected early after plants emerge from tissue culture.